(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Allelopathic influence of three ground-covering plant species (cultivated grasses) has been tested on a culture of apple-trees and their allelopathic influence has been confirmed. Recommendations for decorative plant compositions around apple-trees are provided.